TEKS BERITA KONFLIK PEKERJA PT FREEPORT INDONESIA: ANALISIS WACANA KRITIS FOUCAULT - Yudhi Hari Wibowo (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2013)
ABSTRACT. This study reports a critical discourse analysis on news reports on labour conflicts at PT Freeport Indonesia. The study adopts Foucault’s approaches to critical discourse analysis. According to Foucault, a discourse is an organized language constructing social practice in order to change or to maintain power domination. In this perspective, language is recognized as both the power and the instrument. The analysis article examines the news on the PT Freeport Indonesia labour conflict from the viewpoints of topic, data, theme identification, the search of hidden discourse elements, the search of meaning relationship among the discourse elements, the contextualization of the discourse elements of the power-knowledge network. The results show that the difference of the wages based on biopolical practices under the basis of race discrimination among the Freeport labours triggered the horizontal conflict that was settled under the control of the company. The study also found an indication of a practice of panoptic. This control was effective to settle the conflict because it demanded the obediance productivities on the side of the labours. However, this kind of control camuflased the reality of the Freeport’s massive profit gaining, Freeport’s exploration that damaged the environment, and Timika people’s living in poverty.  Key words: critical discourse analysis, race discrimination, biopolitic, hidden elements, knowledge power